Hubungan Fungsi Sosialisasi Keluarga Terhadap Perilaku Menyimpang Remaja di SMAN 1 KAPUAS TENGAH - Khalilati, Noor; Mathuridy, Roly Marwan; Nurjayanti, Mesti (Journal of Nursing Invention, 2024)
J Background: Deviant behavior is an individual's response or reaction that is reflected in attitudes, either through words or actions that violate, contradict, or deviate from the norms or expectations that exist in the relevant social environment. The family plays a major role in this process, because children's initial interactions occur within the family and their primary contact is limited to their own family members. Objective: This research aims to determine the relationship between the function of family socialization and adolescent deviant behavior at SMAN 1 Kapuas Tengah. Method: The research design is quantitative research with an analytical survey design and approach (cross-sectional). The research population was carried out on all class XI students of SMAN 1 Kapuas Tengah. The sample studied was 145 students using total sampling technique Result: The results of the research show that there is a significant relationship between the family socialization function and adolescent deviant behavior, with a variable significance value of 0.001 which is smaller than 0.05 as a predetermined level (p value < α) which means there is a relationship between the family socialization function which influences adolescent deviant behavior at SMAN 1 Kapuas Tengah. Conclusion: There is a relationship between the function of family socialization and adolescent deviant behavior at SMAN 1 Kapuas Tengah